Aktualisasi Keteladanan Akhlak Nabi Muhammad SAW sebagai Strategi Penguatan Karakter Muslim dalam Merespons Krisis Moral Kontemporer - David Ricardo; Mahmud Arif (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2026)
The contemporary moral crisis, marked by the prevalence of hoaxes, corruption, intolerance, and hedonism, demands a strategic response from the Islamic tradition. This research aims to actualize Prophet Muhammad's (PBUH) moral exemplariness as a strategy for strengthening Muslim character. Using a qualitative literature review method with a thematic-integrative approach, this study analyzes primary sources (the Quran, authentic hadiths, classical Islamic texts) and secondary sources (national and international academic journals). The findings identify five dimensions of Prophetic exemplariness (siddiq, amanah, rahmah, zuhud, hikmah) that directly correspond to 24 character strengths in Peterson and Seligman's Values in Action (VIA) framework. This research formulates four actualization strategies: internalization through contemporary Sufism, behavioral modeling (uswah fi'liyah), moral community reinforcement (al-biah al-shalihah), and Islamic digital literacy. The primary contribution of this research is an integrative model linking Prophetic moral values with modern character psychology, supplemented by an integration table mapping moral crises, Prophetic values, and character-strengthening strategies. This model is intended to serve as an operational framework for Islamic educational institutions, families, and Muslim communities in addressing moral crises systematically and evidence-based.